A composite positive electrode material and its preparation method and application

Through the coating method of silicon source composite aluminum phosphate, the problem of disproportionation reaction of nickel-manganate materials in batteries is solved, and the high-temperature cycling performance of the battery is improved.

CN115863592BActive Publication Date: 2025-05-02SVOLT ENERGY TECHNOLOGY CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202211643687.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-12-20
Publication Date
2025-05-02
Estimated Expiration
2042-12-20

AI Technical Summary

Technical Problem

Nickel-Manganese Oxide materials are prone to disproportionation reactions in batteries, resulting in capacity attenuation and electrolyte decomposition.

Method used

Through the coating method of silicon source composite aluminum phosphate, the coating is carried out using an optimized fluidized bed technology to form a uniform nano-scale coating layer to inhibit side reactions on the surface of the material.

Benefits of technology

It effectively improves the stability of the interface between the electrolyte and lithium nickel manganate, and improves the battery's room temperature and high temperature circulation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115863592B_ABST
    Figure CN115863592B_ABST
Patent Text Reader

Abstract

The present invention provides a composite positive electrode material and a preparation method and application thereof. The preparation method comprises the following steps: (1) mixing aluminum phosphate and a silicon source to obtain an emulsion; (2) mixing the emulsion obtained in step (1) and a positive electrode material to perform fluidized mixing coating to obtain a precursor; (3) sintering the precursor obtained in step (2) to obtain the composite positive electrode material. In view of the fact that lithium nickel manganese oxide materials are prone to disproportionation reactions in batteries, resulting in capacity decay and electrolyte decomposition, the present invention suppresses side reactions on the surface of the material by coating the silicon source composite aluminum phosphate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of lithium ion batteries and relates to a composite positive electrode material and a preparation method and application thereof. Background Art

[0002] Compared with mainstream chemical batteries, lithium-ion batteries have the advantages of high energy density, wide voltage window and long service life, and are widely used in high value-added consumer electronics and power battery fields. In recent years, with the introduction of the concept of carbon neutrality, green and sustainable development has been deeply rooted in the hearts of the people, and a wave of electrification has been set off in the automotive field. As a core component of electric vehicles, the development of high-performance power batteries is also changing with each passing day. In the early days, Yoshino Akira of Japan proposed a coke / lithium cobalt oxide system battery, the commercial mass energy density of which was only 80Wh / kg.

[0003] Positive electrodes include lithium cobalt oxide, lithium iron phosphate, ternary materials, quaternary materials, and cobalt-free positive electrode materials; negative electrodes include soft carbon, hard carbon, and silicon carbon. According to the basic chemical law: energy density = voltage × capacity, high voltage and high capacity are the eternal needs of lithium batteries. Therefore, high-performance lithium-ion batteries represented by high-voltage nickel-manganese nickel-manganese oxide systems and lithium-rich high-manganese layered solid solution systems have attracted widespread interest in the industry.

[0004] Spinel nickel lithium manganese oxide (LiNi 0.5 Mn 1.5 O4) is mainly divided into ordered structure and disordered structure according to the different oxygen vacancies. Among them, the disordered structure has attracted widespread attention because of its good cycle stability. However, because there are more oxygen pores, more trivalent manganese will be brought, and trivalent manganese is prone to the Jan-Taylor effect, generating soluble divalent manganese. On the one hand, the dissolution of divalent manganese leads to the reduction of electrode active substances, which is manifested as the rapid decay of battery capacity; on the other hand, soluble manganese salts will migrate to the negative electrode and affect the stability of SEI, which is manifested as a large amount of gas production in the battery.

[0005] CN104638227A discloses a method for modifying a positive electrode material for a lithium-ion battery, wherein the method uses an aluminum salt or a zirconium salt with a low melting point as an alkali treatment agent, mixes the alkali treatment agent with a lithium-ion battery positive electrode material with a high pH value, and then adopts a two-stage sintering process to obtain a final product. The method effectively reduces residual lithium and pH value, but due to physical mixing, it is difficult to ensure uniformity of coating.

[0006] CN109950498A discloses a high-nickel positive electrode material with a uniform coating layer and a preparation method thereof. The preparation method comprises the following steps: (1) uniformly mixing the high-nickel positive electrode material with a lithium source and a nano-coating material in a solid phase, and sieving to obtain a mixture; (2) placing the mixture in step (1) in a sagger, sintering at a high temperature in a preheated muffle furnace oxygen atmosphere, cooling, crushing, and sieving to obtain a high-nickel positive electrode material with a uniform coating layer. The coating is performed by a solid phase physical mixing method, and it is not easy to ensure the uniformity of the coating. Summary of the invention

[0007] The purpose of the present invention is to provide a composite positive electrode material and a preparation method and application thereof. The present invention aims to suppress the side reactions on the surface of the material by coating with silicon-source composite aluminum phosphate in order to prevent the lithium nickel manganese oxide material from easily undergoing disproportionation reaction in the battery, which leads to capacity decay and decomposition of the electrolyte.

[0008] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:

[0009] In a first aspect, the present invention provides a method for preparing a composite positive electrode material, the preparation method comprising the following steps:

[0010] (1) mixing aluminum phosphate and a silicon source to obtain an emulsion;

[0011] (2) mixing the emulsion obtained in step (1) with the positive electrode material and performing fluidized mixing coating to obtain a precursor;

[0012] (3) Sintering the precursor obtained in step (2) to obtain the composite positive electrode material.

[0013] The present invention adopts optimized fluidized bed technology for coating, and the obtained coating layer is more uniform. The thickness of the silicon dioxide and aluminum phosphate coating layer produced by the decomposition of the selected silicon source and aluminum phosphate emulsion is nanometer level, and the coating layer is uniform and stable, so a smaller addition amount can be used to achieve performance requirements.

[0014] Preferably, the silicon source in step (1) comprises tetraethyl orthosilicate.

[0015] Preferably, the mass ratio of the aluminum phosphate and the silicon source is (0.1-5):(0.5-10), for example: 0.1:1, 0.5:4, 2:8, 3:7, 5:4 or 3:10, etc., preferably (0.5-2):(1-5).

[0016] Preferably, the mass ratio of the emulsion and the positive electrode material in step (2) is (0.6-15):100, for example: 0.6:100, 1:100, 2:100, 5:100, 10:100 or 15:100, etc., preferably (3-8):100.

[0017] Preferably, the positive electrode material comprises a lithium nickel manganese oxide positive electrode material.

[0018] Preferably, in step (2), the emulsion and the positive electrode material are sprayed into a fluidized mixing coating machine via a low-speed airflow.

[0019] Preferably, the pressure of the low-speed airflow is 0.1-1 MPa, for example, 0.1 MPa, 0.3 MPa, 0.5 MPa, 0.8 MPa or 1 MPa.

[0020] Preferably, mixing is continued for 5 to 60 minutes after the addition is completed, for example, 5 minutes, 10 minutes, 20 minutes, 40 minutes or 60 minutes.

[0021] Preferably, the temperature of the fluidized mixing coating in step (2) is 60-150°C, for example, 60°C, 80°C, 100°C, 120°C or 150°C, etc., preferably 85-100°C.

[0022] In the present invention, the selected silicon source is hydrolyzed into silicon dioxide at an appropriate temperature and uniformly adheres to the surface of the positive electrode material, and aluminum phosphate is simultaneously attached to the surface of the particles to obtain a uniformly coated coating layer with a thickness of nanometer level.

[0023] Preferably, the fluidized mixing coating time is 10 to 30 minutes, for example, 10 minutes, 15 minutes, 20 minutes, 25 minutes or 30 minutes.

[0024] Preferably, the temperature of the sintering treatment in step (3) is 500-1000°C, for example, 500°C, 600°C, 700°C, 800°C, 900°C or 1000°C.

[0025] Preferably, the sintering treatment time is 3 to 8 hours, for example: 3 hours, 5 hours, 6 hours, 7 hours or 8 hours.

[0026] Preferably, the atmosphere of the sintering process includes air and / or an inert atmosphere.

[0027] In a second aspect, the present invention provides a composite positive electrode material, which is prepared by the method described in the first aspect.

[0028] Preferably, the composite positive electrode material comprises a nickel cobalt lithium manganese oxide core and a composite coating layer arranged on the surface of the nickel cobalt lithium manganese oxide core, and the composite coating layer comprises silicon dioxide and aluminum phosphate.

[0029] The residual lithium content on the surface of lithium nickel manganese oxide material is extremely low. Using only silicon source cannot coat the base material well. However, using an emulsion containing aluminum phosphate can make the coating more uniform due to the viscosity effect. The silicon dioxide formed by the hydrolysis of the silicon source and the aluminum phosphate act synergistically.

[0030] In a third aspect, the present invention provides a positive electrode plate, wherein the positive electrode plate comprises the composite positive electrode material as described in the second aspect or 8.

[0031] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the lithium-ion battery comprises the positive electrode sheet as described in the third aspect.

[0032] Compared with the prior art, the present invention has the following beneficial effects:

[0033] (1) The present invention aims to address the problem that lithium nickel manganese oxide materials are prone to disproportionation reactions in batteries, which lead to capacity decay and electrolyte decomposition. The method of silicon-source composite aluminum phosphate coating is used to suppress side reactions on the material surface.

[0034] (2) The present invention can effectively improve the stability of the interface between the electrolyte and lithium nickel manganese oxide through the method of silicon source composite aluminum phosphate coating, and improve the room temperature and high temperature cycle performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0035] Figure 1 This is a SEM image of the composite positive electrode material described in Example 1.

[0036] Figure 2 This is a SEM image of the positive electrode material described in Comparative Example 1.

[0037] Figure 3 This is the SEM image of the positive electrode material described in Comparative Example 2. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0039] Example 1

[0040] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0041] (1) Add 10 g of aluminum phosphate to 40 g of tetraethyl orthosilicate and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0042] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 90° C. and the reaction time is 20 min to obtain a precursor material;

[0043] (3) The precursor material obtained in step (2) was heated to 900°C in an air atmosphere, sintered for 5 hours, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material. The SEM image of the composite positive electrode material is as follows Figure 1 shown.

[0044] Example 2

[0045] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0046] (1) Add 20 g of aluminum phosphate to 30 g of tetraethyl orthosilicate and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0047] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 90° C. and the reaction time is 20 min to obtain a precursor material;

[0048] (3) The precursor material obtained in step (2) is heated to 900° C. in an air atmosphere, sintered for 5 h, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material.

[0049] Example 3

[0050] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0051] (1) Add 25 g of aluminum phosphate to 25 g of ethyl orthosilicate, and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0052] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 90° C. and the reaction time is 20 min to obtain a precursor material;

[0053] (3) The precursor material obtained in step (2) is heated to 900° C. in an air atmosphere, sintered for 5 h, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material.

[0054] Example 4

[0055] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0056] (1) Add 5 g of aluminum phosphate to 45 g of ethyl orthosilicate and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0057] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 90° C. and the reaction time is 20 min to obtain a precursor material;

[0058] (3) The precursor material obtained in step (2) is heated to 900° C. in an air atmosphere, sintered for 5 h, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material.

[0059] Example 5

[0060] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0061] (1) Add 1 g of aluminum phosphate to 49 g of tetraethyl orthosilicate and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0062] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 90° C. and the reaction time is 20 min to obtain a precursor material;

[0063] (3) The precursor material obtained in step (2) is heated to 900° C. in an air atmosphere, sintered for 5 h, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material.

[0064] Example 6

[0065] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0066] (1) Add 10 g of aluminum phosphate to 40 g of tetraethyl orthosilicate and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0067] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 120° C. and the reaction time is 20 min to obtain a precursor material;

[0068] (3) The precursor material obtained in step (2) is heated to 900° C. in an air atmosphere, sintered for 5 h, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material.

[0069] Example 7

[0070] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0071] (1) Add 10 g of aluminum phosphate to 40 g of tetraethyl orthosilicate and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0072] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 80° C. and the reaction time is 20 min to obtain a precursor material;

[0073] (3) The precursor material obtained in step (2) is heated to 900° C. in an air atmosphere, sintered for 5 h, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material.

[0074] Example 8

[0075] This embodiment provides a composite positive electrode material, and the preparation method of the composite positive electrode material is as follows:

[0076] (1) Add 10 g of aluminum phosphate to 40 g of tetraethyl orthosilicate and stir at 1000 rpm for 10 min to form a uniform emulsion;

[0077] (2) nitrogen gas with an emulsion pressure of 0.2 MPa is introduced into a fluidized bed reactor in which 1 kg of spinel nickel manganese oxide positive electrode material is suspended, and the pressure in the reaction chamber reaches 5 mbar. The temperature of the reactor is controlled at 90° C. and the reaction time is 40 min to obtain a precursor material;

[0078] (3) The precursor material obtained in step (2) is heated to 900° C. in an air atmosphere, sintered for 5 h, cooled to room temperature in the furnace, and sieved to remove magnetism to obtain the composite positive electrode material.

[0079] Comparative Example 1

[0080] This comparative example uses an uncoated spinel nickel manganese oxide positive electrode material. The SEM image of the positive electrode material is as follows: Figure 2 shown.

[0081] Comparative Example 2

[0082] The only difference between this comparative example and Example 1 is that aluminum phosphate is not added, and the other conditions and parameters are exactly the same as those of Example 1. The SEM image of the obtained positive electrode material is as follows: Figure 3 shown.

[0083] Comparative Example 3

[0084] The only difference between this comparative example and Example 1 is that conventional grinding and coating is adopted, and other conditions and parameters are exactly the same as those in Example 1.

[0085] Performance Test:

[0086] The positive electrode sheets prepared in the above-mentioned embodiments and comparative examples were used to make 2Ah soft-pack batteries.

[0087] The preparation process of the positive electrode sheet is as follows: the prepared positive electrode main material, conductive agent (SP) and binder (PVDF) are mixed evenly in a mass ratio of 96:2:2 to prepare a slurry with a solid content of 75%. The current collector is a 12-micron thick aluminum foil. After the slurry is applied, roller pressed and dried, a 65-micron thick positive electrode sheet is obtained. The diaphragm is a PE diaphragm. The electrolyte is a conventional fluorine-containing high-voltage electrolyte. The rated capacity of the soft-pack battery is 2Ah.

[0088] The preparation process of the negative electrode sheet adopted is: graphite, conductive agent (SP), binder CMC and binder SBR are mixed evenly in a mass ratio of 96.5:1.5:1.5:1.5 to prepare a slurry with a solid content of 50%, and an 8-micron thick copper foil is selected as the current collector. After the processes of slurry coating, roller pressing and drying, a negative electrode sheet with a thickness of 70 microns is obtained.

[0089] The soft-pack battery prepared above was tested for the first discharge capacity (mAh / g), the first coulombic efficiency (%), the 50-week cycle retention rate (%, 25°C) and the 50-week cycle retention rate (%, 45°C). The test results of each embodiment and comparative example are shown in Table 1:

[0090] Table 1

[0091]

[0092]

[0093] As can be seen from Table 1, from Examples 1-2, the first discharge specific capacity of the battery made of the composite positive electrode material of the present invention can reach more than 148.2 mAh / g, the first coulombic efficiency can reach more than 96.1%, the 25°C 50-week cycle retention rate can reach more than 99.1%, and the 45°C 50-week cycle retention rate can reach more than 98.2%.

[0094] By comparing Example 1 with Examples 3-5, it can be seen that in the preparation process of the composite positive electrode material of the present invention, the mass ratio of aluminum phosphate and the silicon source will affect the performance of the prepared positive electrode material. When the mass ratio of aluminum phosphate and the silicon source is controlled at (0.5-2):(1-5), the performance of the prepared composite positive electrode material is better. If the amount of aluminum phosphate added is too large, the coating layer of the positive electrode material is uneven. If the amount of silicon source added is too large, the internal resistance of the battery is seriously increased, which is not conducive to improving the electrical performance of the battery.

[0095] By comparing Example 1 with Examples 6-7, it can be seen that in the preparation process of the composite positive electrode material of the present invention, the temperature of the fluidized mixing coating will affect the performance of the composite positive electrode material. The temperature of the fluidized mixing coating is controlled at 85-100°C, and the performance of the positive electrode material is better. If the temperature is too high, the aluminum phosphate and the silicate decompose too quickly, and a uniform coating layer cannot be obtained. If the temperature is too low, the aluminum phosphate and the silicate are not completely decomposed, the coating layer is thin, the protection of the positive electrode material is weak, and the battery cycle performance cannot be effectively improved.

[0096] By comparing Example 1 and Example 8, it can be seen that the coating effect of the fluidized mixing coating of the present invention will decrease to a certain extent after the time reaches 30 minutes, and the time of the fluidized mixing coating needs to be controlled within 20 to 30 minutes.

[0097] By comparing Example 1 and Comparative Example 1, it can be seen that the present invention suppresses side reactions on the surface of the material through the method of silicon source composite aluminum phosphate coating, the thickness of the silicon dioxide and aluminum phosphate coating layer produced by the decomposition of the silicon source and aluminum phosphate emulsion is nanometer level, the coating layer is uniform and stable, and the stability of the material can be significantly improved.

[0098] From the comparison between Example 1 and Comparative Example 2, it can be seen that the base material cannot be well coated by simply using tetraethyl orthosilicate, while the coating is more uniform by using an emulsion containing aluminum phosphate due to the effect of viscosity.

[0099] From the comparison between Example 1 and Comparative Example 3, it can be seen that the present invention adopts optimized fluidized bed technology for coating, and the obtained coating layer is more uniform compared with the traditional grinding coating.

[0100] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention shall fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a composite positive electrode material, characterized in that: The preparation method comprises the following steps: (1) mixing aluminum phosphate and a silicon source to obtain an emulsion; (2) mixing the emulsion obtained in step (1) with the positive electrode material and performing fluidized mixing coating to obtain a precursor; (3) sintering the precursor obtained in step (2) to obtain the composite positive electrode material; The silicon source in step (1) includes tetraethyl orthosilicate.

2. The preparation method according to claim 1, characterized in that The mass ratio of the aluminum phosphate to the silicon source is (0.1-5):(0.5-10).

3. The preparation method according to claim 2, characterized in that: The mass ratio of the aluminum phosphate and the silicon source is (0.5-2):(1-5).

4. The preparation method according to claim 1, characterized in that: The mass ratio of the emulsion and the positive electrode material in step (2) is (0.6-15):

100.

5. The preparation method according to claim 4, characterized in that: The mass ratio of the emulsion and the positive electrode material in step (2) is (3-8):

100.

6. The preparation method according to claim 1, characterized in that: The positive electrode material includes a lithium nickel manganese oxide positive electrode material.

7. The preparation method according to claim 1, characterized in that: In step (2), the emulsion and the positive electrode material are sprayed into a fluidized mixing coating machine through a low-speed airflow.

8. The preparation method according to claim 7, characterized in that: The pressure of the low-speed airflow is 0.1-1 MPa.

9. The preparation method according to claim 7, characterized in that: After the addition is complete, continue mixing for 5 to 60 minutes.

10. The preparation method according to claim 1, characterized in that: The temperature of the fluidized mixing coating in step (2) is 60-150°C.

11. The preparation method according to claim 10, characterized in that: The temperature of the fluidized mixing coating is 85-100°C.

12. The preparation method according to claim 1, characterized in that: The fluidized mixing coating time is 10 to 30 minutes.

13. The preparation method according to claim 1, characterized in that: The sintering temperature in step (3) is 500-1000°C.

14. The preparation method according to claim 1, characterized in that: The sintering time is 3 to 8 hours.

15. The preparation method according to claim 1, characterized in that: The sintering process atmosphere includes air and / or an inert atmosphere.

16. A composite positive electrode material, characterized in that: The composite positive electrode material is prepared by the method according to any one of claims 1 to 15.

17. The composite positive electrode material according to claim 16, characterized in that: The composite positive electrode material comprises a nickel cobalt lithium manganese oxide core and a composite coating layer arranged on the surface of the nickel cobalt lithium manganese oxide core, wherein the composite coating layer comprises silicon dioxide and aluminum phosphate.

18. A positive electrode plate, characterized in that: The positive electrode sheet comprises the composite positive electrode material as claimed in claim 16 or 17.

19. A lithium ion battery, characterized in that: The lithium-ion battery comprises the positive electrode sheet as claimed in claim 18.

Citation Information

Patent Citations

  • Method for modifying positive electrode material of lithium ion battery

    CN104638227A

  • High-nickel positive electrode material with uniform coating layer and preparation method thereof

    CN109950498A

  • Method for preparing spinel type lithium manganate coated with metal oxide

    CN106784682A

  • Phosphorus aluminum coating lithium titanate composite material and preparation method thereof

    CN109713283A